Sodomites, invertis, homosexuels: perspectives historiques - Mendès-Leite, Rommel (Cahiers Gai-Kitsch-Camp, 1994)
Section: 193 pages : illustrations ; 21 cm
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques